Pengaruh Media dan Jenis Dekomposer Cacing Tanah (lumbricus rubellus) dan Larva Black soldier fly terhadap Mutu Pupuk Organik - PAMUNGKAS, ACMAD PRASETYO; KARTINI, NI LUH; SONIARI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Effect of Media and Decomposer Types ( Lumbricus rubellus ) Earthworms and Black soldier fly Larvae on the Quality of Organic Fertilizer Based on data from the Bali Provincial Environmental Service in 2018, it is revealed that every day Bali produces 10,849.10 m 3 / day of waste. The aim of this study was to determine the effect of media and type of decomposer on the quality of organic fertilizers and the percentage of organic matter decomposition. This research was started from January - March 2020 in the village of Megati, Tabanan Regency, the treatment consisted of nine media and types of decomposers with three replications with a total of 27 treatments using a simple randomized block design (RBD), namely the treatment without other decomposer mixtures plus the type of decomposer. 0.10 g BSF maggot, 0,20 g BSF maggot, 250 g worm, and 500 g worm, and the media uses fruit waste without chicken manure and other cow dung, fruit waste plus chicken and cow manure. Media and type of decomposer affect the percentage of organic matter decomposition, shown in the treatment of 2 kg of organic waste + 1 kg of cow dung + 0,20 g of maggot and 2 kg of organic waste + 1 kg of cow dung + 250 g of worms. the highest decomposed percentage was 86%. Control (3 kg organic waste) percentage of decomposition 26%, an increase of 60%.